KASITS: A Graphical User Interface for Kinematic Analysis and Synthesis of Five-Bar Linkage with Prismatic Joint - Taufik Ali Rahman; Achmad Saiful Hadi; Latifah Nurahmi; Ari Kurniawan Saputra; Bambang Pramujati; Unggul Wasiwitono; Arockia Selvakumar (JMES The International Journal of Mechanical Engineering and Sciences, 2021)
In this paper, a novel graphical user interface is developed for kinematic analysis and synthesis of five-bar linkage with prismatic joint, named KASITS. This interface has two menus that the users can freely select, namely for analysis and synthesis. In the analysis menu, the direct kinematics are derived to visually depict the overall workspace of the mechanism. Within this workspace, the singularity curves are plotted. In the synthesis menu, the value of design parameters is obtained for a given trajectory. An optimization is employed based on Pareto optimal solutions. The demonstration is provided to guide the users better.